A chronology of the works of Guillaume Dufay based on a study of mensural practice - Hamm, Charles (Princeton, New Jersey Princeton university press, 1964)
Although, according to the author, much sound research, has been done in the Dufay era in recent years," Charles Hamm's book marks the first time an attempt has been made at a comprehensive chronology of the works of this composer. Professor Hamm approaches all Dufays compositions from the point of view of mensural practice, and has been able to date each piece more precisely than would have been possible in a chronology based on manuscript studies or stylistic analyses. He has divided the works into nine groups, according to details of mensural usage, and on the basis of datable works and other evidence has suggested dates within which the pieces of each group were written. Based on his study of Dufays mensural practice, the author suggests that the Missa Sancti Antoni and several other works attributed to Dufay may not have been written by him.